The Third World And International Law - Jewa, Tunku Sofiah (Journal of Malaysian and Comparative Law, 2018)
The Third World is attempting to extort - through economic blackmail, moral bullying, and outright theft - a portion of the West’s legitimacy acquired wealthy. - Patrick Moyniban (Former U.S. Ambassador to the United Nations)